IMPLICATIONS OF MENTAL TRAINING ON SELF-CONFIDENCE AND ANXIETY AMONG FEMALE STUDENTS AT AL-MUHAJIRIN ISLAMIC BOARDING SCHOOL - Atri Widowati; Fitri Diana; Mhd. Usni Zamzami Hasibua; Grafitte Decheline; Sri Murniati; Yonifia Anjanik (Journal of Sport Science and Tourism Activity, 2026)
This study aimed to analyze the implications of mental training on self-confidence and anxiety among female students at Al-Muhajirin Islamic boarding school. The research employed an experimental method with a one group pretest-posttest design. The subjects consisted of 30 female students selected using purposive sampling. The intervention involved mental training consisting of relaxation and concentration techniques conducted over four weeks. The research instruments included self-confidence and anxiety scales, and data were analyzed using the paired sample t-test. The results showed an increase in the mean score of self-confidence from 65.4 to 78.9 and a decrease in anxiety from 72.1 to 60.3. Statistical analysis indicated that the increase in self-confidence (t = 5.87; p < 0.05) and the decrease in anxiety (t = -6.12; p < 0.05) were significant. Therefore, mental training has positive implications for improving self-confidence and reducing anxiety among female students.